Kualitas dan Interpretasi Hadis Makan Sambil Bersandar: Studi Takhrij dan Syarah Hadis - Indi Ariqah Putri Dadi (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about eating while leaning. This study uses a qualitative approach by applying descriptive analytical method. The formal object of this research is the science of hadith, while the material object is about eating while relying on the history of Bukhari no. 4980. These results and discussion show the status of hasan li ghairihi quality hadith that meet the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the Hadith of Bukhari No. 4980 is relevant used as learning in everyday life so that we do not make mistakes in eating procedures.